The origin and evolution of the ribosome - Gutell Robin R; Lee Jung C; Smith Temple F; Hartman Hyman (Biology Direct, 2008)
Abstract Background The origin and early evolution of the active site of the ribosome can be elucidated through an analysis of the ribosomal proteins' taxonomic block structures and their RNA interactions. Comparison between the two subunits, exploiting the detailed three-dimensional structures of the bacterial and archaeal ribosomes, is especially informative. Results The analysis of the differences between these two sites can be summarized as follows: 1) There is no self-folding RNA segment that defines the decoding site of the small subunit; 2) there is one self-folding RNA segment encompassing the entire peptidyl transfer center of the large subunit; 3) the protein contacts with the decoding site are made by a set of universal alignable sequence blocks of the ribosomal proteins; 4) the majority of those peptides contacting the peptidyl transfer center are made by bacterial or archaeal-specific sequence blocks. Conclusion These clear distinctions between the two subunit active sites support an earlier origin for the large subunit's peptidyl transferase center (PTC) with the decoding site of the small subunit being a later addition to the ribosome. The main implications are that a single self-folding RNA, in conjunction with a few short stabilizing peptides, formed the precursor of the modern ribosomal large subunit in association with a membrane. Reviewers This article was reviewed by Jerzy Jurka, W. Ford Doolittle, Eugene Shaknovich, and George E. Fox (nominated by Jerzy Jurka).